ORDER CONTROL DESIGN COMPUTERIZED SYSTEM PRINTS ON CV. MUSADY - Slamet Slamet; Fitri Sjafrina Ir. MMSI (Jurnal Sistem Informasi, 2000)
With existence of computerized system is expected that the existing service system during and after computer manual will be faster to deal with problems accessing customer data and customer data search. These enterprises can be run well, it is necessary vital information such as customer lists, order lists, list all of which were to support such enterprises in the process. Given the activities necessary to design in a business entity "CV. Musady" The academy will look good impact at this time includes making the next customer data stored in computer storage of data, orders data already exists in the customer file dab so the cost of incoming invoices known in the business, through supporting software Microsoft Access 1997.